Physical and Chemical Properties of Lithium Slag and Experiment on Preparation of Artificial Aggregate Using Alkali-activation - Zhou ZOU; Liang SONG; Xiaodong XIE; Lulu HOU; Jie GAO (Kuangchan zonghe liyong, 2024)
This is an article in the field of ceramics and composites. With the growth of lithium smelting scale in China, the production of lithium slag increases year by year, the need for its resource utilization is becoming more and more obvious. To explore the physical and chemical properties of lithium slag and its potential as a cementitious material to prepare artificial aggregate, the composition and properties of lithium mica lithium slag in Yichun, China and lithium slag from spodumene in Australia were characterized, and their effects on alkali excitation performance were analyzed. Secondly, two kinds of lithium slag artificial aggregates were prepared by disk cold granulation method with sodium hydroxide as alkali activator, and their compressive strength was tested. Finally, the environmental risks of artificial aggregates were demonstrated by glass electrode method, inductively coupled plasma mass spectrometry, ion chromatography and spectrophotometry. The results show that the physical and chemical properties of lithium mica lithium slag are more suitable for the preparation of artificial aggregates by alkali excitation than lithium pyroxene lithium slag, and the resulting artificial aggregates are stronger and the liquid leachate is not environmentally hazardous.